Flexural Performance of Glued Laminated Timber Beams Reinforced with Externally Bonded FRP: An Experimental Investigation - Dani Nugroho Saputro; Eva Ariyanti; Nor Intang Setyo Hermanto; Hery Awan Susanto (Jurnal Teknik Sipil dan Lingkungan, 2025)
The use of hard timber in construction is increasing, but it is quite expensive and its production is slow. As an alternative, laminated timber combining hard and soft quality timber has been proposed. This study utilized rambutan timber (hardwood) and sengon timber (softwood). Structural failure may occur when elements can no longer resist the applied loads; thus, reinforcement is required. This study aims to investigate the flexural strength of laminated timber beams and assess the performance enhancement using a fiber-reinforced polymer (FRP) type SCH-11UP. Composite was applied through the Externally Bonded (EB) method. The flexural capacity was evaluated in accordance with ASTM D143 through four-point bending tests and SNI 7973:2013. Four types of test objects were tested with three samples per type: TP (unreinforced), EB1 (type 1), EB2 (type 2), and EB3 (type 3), with TP as the control group. The experimental results showed that EB3 yielded the highest improvement, with up to 87% increase in the maximum load capacity, displacement, modulus of elasticity (MOE), modulus of rupture (MOR), stiffness, and structural efficiency. The improvements followed in descending order: EB2, EB1, and TP.